Strategic language crossing as self-styling: the case of black African immigrants in South Africa. Issue 4 (2nd October 2019) - Makoni, Busi
ABSTRACT: This study focuses on the ways in which black African immigrants (BAIs) in Johannesburg claim ethnic identities through strategic practices involving multiple affordances that go beyond language competence. Drawing on a qualitative study consisting of data from interviews with BAIs, this article argues that BAIs claim specific ethnic identities through self-styling, for instance, wearing clothes they perceive to be 'ethnic' style markers and in some cases bleaching their skin as part of their in-group identity work. Extending the idea of language crossing, the article contends that although these practices resemble elements of crossing, BAIs are not necessarily taking on out-group ethnic identity markers as would be the case in language crossing; instead, these practices are for in-group self-identification and extend beyond tokens to other affordances. These self-styling practices do not necessarily represent solidarity or identification with a particular group per se, but rather, are indicative of a strategic choice necessitated by the state of precarity which BAIs face in South Africa. The conclusion drawn from these practices is that self-styling disarticulates the close relationship between language and ethnicity, allowing BAIs to claim an ethnic identity even in instances where they have limited or no proficiency in the relevant language.